2019
DOI: 10.1080/23752696.2019.1644659
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the ‘wicked’ problem of student dissatisfaction with assessment and feedback in higher education

Abstract: Student dissatisfaction with assessment and feedback is a significant challenge for most UK Higher Education Institutions according to a key national survey. This paper explores the meaning, challenges and potential opportunities for enhancement in assessment and feedback within the authors' own institution as illustrative of approaches that can be taken elsewhere. Using a qualitative design, a review of assessment and feedback, which included an exploration of students' perceptions, was made in one College of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 48 publications
1
33
1
3
Order By: Relevance
“…In the current study’s setting, nursing students perceived that there are uniformities in the nature and manner of how feedback is conveyed to the nursing students. These findings are contrary to those of Deeley et al ( 2019 :385–405), who asserted that students noted inconsistency in the way feedback was conveyed by different staff. This recommendation on the development of procedures and guidelines for feedback is crucial, considering that registered nurses are not trained as clinical educators and a large number of lecturers, tutors and clinical instructors are appointed in their positions because of qualifications in their discipline that are, however, not education-related.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…In the current study’s setting, nursing students perceived that there are uniformities in the nature and manner of how feedback is conveyed to the nursing students. These findings are contrary to those of Deeley et al ( 2019 :385–405), who asserted that students noted inconsistency in the way feedback was conveyed by different staff. This recommendation on the development of procedures and guidelines for feedback is crucial, considering that registered nurses are not trained as clinical educators and a large number of lecturers, tutors and clinical instructors are appointed in their positions because of qualifications in their discipline that are, however, not education-related.…”
Section: Discussioncontrasting
confidence: 98%
“…In addition, students feel insulted and undermined as a result of feedback given in groups. Conflicting results were documented by Deeley et al ( 2019 :385–405), who revealed that students find it beneficial to receive group feedback. Nevertheless, Hardavella et al ( 2017 :327–333) indicated that feedback providers may give group feedback, but this should be addressed to the whole group rather than targeting an individual within the group.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Addressing the wicked problem of feedback during the teaching practicum Gravett, 2020). Research has highlighted the inadequacies of the feedback provided to student teachers during the teaching practicum (Deeley et al, 2019;Ellis & Loughland, 2017). By their very nature, wicked problems involve numerous stakeholders, each with different perspectives on the problem, its causes and possible ways of addressing the problem.…”
Section: Nel and Maraismentioning
confidence: 99%